ANALISIS PENERAPAN WILAYAH KERJA PPAT BERDASARKAN PERATURAN PEMERINTAH NOMOR 24 TAHUN 2016 TENTANG PERUBAHAN ATAS PERATURAN PEMERINTAH NOMOR 37 TAHUN 1998 DI PROVINSI DKI JAKARTA - Ivandi Setiawan; Rasji . (Fakultas Hukum Universitas Tarumanagara, 2018)
PPAT is a public official authorized to make authentic deeds concerning certain legal acts concerning the right to land or the Property Right of the Flats Unit. Government Regulation No. 24 of 2016 is the latest regulation made by the government to regulate provisions on PPAT. in Government Regulation No. 24 of 2016 in Article 12 paragraph one explained that the scope of work area of PPAT is expanded into one province where in the previous regulation that is government regulation number 37 year 1998 explained that the scope of work of PPAT is only limited to district only. but the fact is now the government regulation number 24 of 2016 has not been applied efficiently, especially in terms of the scope of work of PPAT, it happens because of several factors that hamper causing the loss of effectiveness in Article 12 Paragraph one of Government Regulation No. 24 of 2016 . it is of course also contrary to the legal certainty that the public should have legal certainty with the enactment of the government regulation number 24 of 2016 by the government then the regulation should be applicable in the scope of the working area of PPAT should be applicable in practice in the community. contrary to lex posterior derogate legi priori principle which explains that in the same rules the new rules can replace the old rules. the approach used in this study using the approach of law.